2014
DOI: 10.1016/j.intacc.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The Real and Accrual-based Earnings Management Behaviors: Evidence from the Split Share Structure Reform in China

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
116
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 76 publications
(157 reference statements)
18
116
1
4
Order By: Relevance
“…Using some regression techniques, the study has detected some positive and meaningful relationships between earnings forecast as well as actual earnings and growth domestic product. The results of this study are consistent with findings earlier reported in the literature (Campello et al, 2010;Kuo et al, 2014).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Using some regression techniques, the study has detected some positive and meaningful relationships between earnings forecast as well as actual earnings and growth domestic product. The results of this study are consistent with findings earlier reported in the literature (Campello et al, 2010;Kuo et al, 2014).…”
Section: Resultssupporting
confidence: 94%
“…Other literature report that earnings forecasts assist us to cut through the fog of economic uncertainty and are encouraged to help users specifically during such periods (Anilowski et al, 2010). Kuo et al (2014) studied the earnings management activities in Chinese listed companies and the effect of the split share structure reform (SSSREF). They explained that Chinese listed companies represented a long-term positive relationship between real and accrual-based earnings management activities.…”
Section: Introductionmentioning
confidence: 99%
“…For the author, decisions based on operating activities aff ect company cash fl ow and can also aff ect discretionary accruals. Along this same line of thinking, Kuo, Ning, and Song (2014) argue that management based on operating activities is related to governance mechanisms, in which strong and eff ective governance tends to increase investor protection and the quality of fi nancial information, intensifying control in the capital market.…”
Section: Earnings Managementmentioning
confidence: 99%
“…Thus, a new stream of research examined REM and AEM at the same time. These studies have shown evidence for the trade-off between the two earnings management according to, for example, the Sarbanes-Oxley Act (SOX) adoption (Cohen et al 2008), the seasoned equity offering (SEO) (Cohen and Zarowin 2010), the overvaluation (Badertscher 2011), their relative costliness (Zang 2012), the split share structure reform (Kuo et al 2014). Regarding the context of the mandatory IFRS adoption, the relation between REM and AEM was not well examined until recent years.…”
Section: Introductionmentioning
confidence: 99%